Investigation on solid particle erosion behaviour of polyetherimide and its composites - Harsha A.P.; Thakre A.A. (My University, 2025)
The present investigation reports about, the solid particle erosion behaviour of randomly oriented short E-glass, carbon fibre and solid lubricants (PTFE, graphite, MoS2) filled polyetherimide (PEI) composites. The erosion rates (ERs) of these composites have been evaluated at different impingement angles (15-90°) and impact velocities (30-88 m/s). Mechanical properties such as tensile strength (S), ultimate elongation to fracture (e), hardness (HV), Izod impact strength (I) and shear strength (Ss) seems to be controlling the erosion rate of PEI and its composites. Polyetherimide and its glass, carbon fibre reinforced composites showed semi-ductile erosion behaviour with peak erosion rate at 60° impingement angle. However, glass fibre reinforced PEI composite filled with solid lubricants showed peak erosion rate at 60° impingement angle for impact velocities of 30 and 88 m/s, whereas for intermediate velocities (52 and 60 m/s) peak erosion rate observed at 30° impingement angle. It is observed that 20% (w/w) glass fibre reinforcement helps in improving erosive wear resistance of neat PEI matrix. Erosion efficiency (η) values (0.23-8.2%) indicate micro-ploughing and micro-cutting dominant wear mechanisms. The morphology of eroded surfaces was examined by using scanning electron microscopy (SEM). Possible erosion mechanisms are discussed. © 2006 Elsevier B.V. All rights reserved.